From Gene to Clinic: The Role of APOL1 in Focal Segmental Glomerulosclerosis - Charlotte Delrue; Marijn M. Speeckaert (Sclerosis)
Apolipoprotein L1 (APOL1) genetic variations, notably the G1 and G2 alleles, have important roles in the pathophysiology of focal segmental glomerulosclerosis (FSGS) and other kidney problems, especially in people of African descent. This review summarizes current understanding about the genetic, molecular, and clinical features of APOL1-associated FSGS and investigates new therapeutic options. It reveals how APOL1 mutations generate kidney injury through mechanisms such as podocyte dysfunction, mitochondrial impairment, and dysregulated inflammatory networks. Recent treatment developments, such as small-molecule inhibitors like inaxaplin, antisense oligonucleotides, and novel interventions targeting lipid metabolism and inflammatory pathways, are being assessed for their capacity to address the specific issues presented by APOL1-associated nephropathy. We also address gaps in knowledge, such as the function of environmental triggers and the systemic consequences of APOL1 mutations, emphasizing the significance of targeted research.